Dampak Perceraian pada Perkawinan Campuran Suku Jawa Minang terhadap Hak Asuh Anak Perspektif Hukum Keluarga Islam di Kota Padang Panjang - Asep Saepul Mikdar; Badoar Hasibuan (CV. ALIM'SPUBLISHING, 2026)
This study examines the issue of child custody following divorce among Javanese and Minangkabau couples, resulting from differences in kinship systems that trigger conflicts between customary law, Islamic law, and the best interests of the child. The study aims to analyze the impact of divorce in Javanese-Minangkabau mixed marriages on child custody following divorce in the city of Padang Panjang, with a focus on the perspectives of Islamic law and local customary law. This is a qualitative study using a case study approach. Data collection was conducted through interviews. Informants included traditional leaders, officials of Javanese associations, married couples in mixed marriages, and divorced couples who are raising children. The data analysis technique used to test data validity was triangulation. The research results indicate that differences in kinship systems between the patrilineal Javanese and the matrilineal Minangkabau influence the determination of child custody following divorce. In practice, child custody is often influenced by supporting and inhibiting factors. Supporting factors are evident when Javanese couples reside in a Minangkabau environment, leading them to follow local customs that require the husband to live in the wife’s family home. Conversely, obstacles arise when a divorce occurs, as children tend to stay with their mother because the home is located on the wife’s family land. From the perspective of Islamic law, the principle of maslahah serves as the primary foundation, prioritizing the child’s overall well-being. Additionally, local customs such as extended family consultations are often used to resolve conflicts. However, challenges such as the father’s failure to fulfill child support obligations still persist. Therefore, the integration of Islamic law and customary law, along with enhanced mediation efforts, is necessary to safeguard children’s rights.